2007
DOI: 10.1590/s0037-86822007000500004
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal profile and level of CD4+ lymphocytes in the occurrence of cryptosporidiosis and cystoisosporidiosis in HIV/AIDS patients in the Triângulo Mineiro region, Brazil

Abstract: Patients with AIDS are particularly susceptible to infection with intestinal coccidia. In this study the prevalence of infections with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 17 publications
2
21
0
5
Order By: Relevance
“…Although the occurrence of cryptosporidiosis cases did not differ statistically between seasons, the results are consistent with other studies reporting a higher frequency of cryptosporidiosis in the hotter and more humid months of the year 19,30,32 . This seasonal pattern was not observed for cystoisosporosis, whose chronic character and recurrences are believed to be due to the ability of C. belli to infect extraintestinal sites, where the parasite forms tissue cysts that eventually return to the intestine and trigger new pathogenic processes.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Although the occurrence of cryptosporidiosis cases did not differ statistically between seasons, the results are consistent with other studies reporting a higher frequency of cryptosporidiosis in the hotter and more humid months of the year 19,30,32 . This seasonal pattern was not observed for cystoisosporosis, whose chronic character and recurrences are believed to be due to the ability of C. belli to infect extraintestinal sites, where the parasite forms tissue cysts that eventually return to the intestine and trigger new pathogenic processes.…”
supporting
confidence: 91%
“…According to OLIVEIRA-SILVA et al 19 , low CD4 + T lymphocyte counts are a predisposing factor for protozoal infections. This was demonstrated in the present study in which all patients with cryptosporidiosis or cystoisosporosis had low lymphocyte counts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In India, studies conducted in twin cities of Hyderabad and Secunderabad indicated that children in the age group of six months to one year were the most vulnerable with 14.3% infections compared to 8.2% among children less than five years of age while in Malaysia the prevalence was 7.5% and 33.3% in Egypt (Nagamani et al, 2007;Al-Mekhlafi et al, 2011). It has been demonstrated in some countries such as Mexico (Javier-Enriquez et al, 1997), Brazil (Newman et al, 1999;de Oliveira-Silva et al 2007), and Indonesia (Katsumata et al, 2000;Moyo et al, 2011) that Cryptosporidium transmission in children is usually associated with the rainy season, and waterborne transmission is considered a major route in the epidemiology of cryptosporidiosis in these areas. Although water contamination with Cryptosporidium has been demonstrated in other parts of South Africa, such research needs to be completed in the Limpopo Province in order to confirm the source of transmission in the region.…”
Section: Discussionmentioning
confidence: 98%
“…Administration of Highly Active Anti Retroviral Therapy would lower the HIV viraemia; boost the immune response thus leading to clearance of these parasites. Several studies were carried out in India 1,2 and abroad 3,4,5 to correlate the immune status and treatment status of HIV patients with the prevalence of these parasitic infections. The present study was carried out to evaluate the role of the treatment status, immune status and duration of diarrhoea as predictors of acquiring coccidian infections in HIV/AIDS patients.…”
Section: Introductionmentioning
confidence: 99%